KLASIFIKASI DATA MINING DI TINGKAT KEPUASAN MAHASISWA TERHADAP PELAYANAN SISTEM INFORMASI FAKULTAS TEKNIK UNIVERSITAS NURUL JADID - Zain, Ahmad Naufal Waliyus; Muafi, Muafi; Tholib, Abu (Universitas Budi Luhur, 2024)
This research aims to assess impacts of information system services on student satisfaction to prevent dissatisfaction with campus information services. Students become active members of the academic community at higher education, are the center point of this investigation. Because the measurement of student satisfaction level on information services at the Faculty of Engineering is still unknown. By measuring student satisfaction, the faculty can improve the quality of service information system. The importance of campus information system services cannot be overstated because it serves as the main center for information management in higher education. in higher education. By using the Naïve Bayes Algorithm for the method used in this research utilizes simplicity and ease of application. its application. Data was collected through a questionnaire technique filled out by students of faculty of Engineering. The questionnaire contains about the quality of information systems and information service quality. A total of 316 student datasets were collected from 3 study programs in the Faculty of Engineering namely informatics, electrical engineering, and information technology study programs. Testing using naïve Bayes algorithm accuracy value of 94%, precision of 92% recall of 95%, and f1-score of 93%. It is hoped that this research can play an important role in improving the existing information system services to increase effectiveness. information system services to increase effectiveness.